Accuracy of cranial ultrasound in the diagnosis of hydrocephalus in children under 6 months of age keeping CT scan as a gold standard - Rabia Ikram, Rabia Ikram; Amina Khalid, Amina Khalid; Wasif Farman, Wasif Farman; Fazal Hussain Shah, Fazal Hussain Shah; Hina Baig, Hina Baig; Sadaf Ajaib, Sadaf Ajaib (Journal of Rawalpindi Medical College, 2020)
Introduction: CT and MRI modalities are considered a gold standard for the diagnosis of hydrocephalus. The more readily available and cheap options like sonography are being sought out for the diagnosis of this entity. Objectives: To determine the accuracy of cranial ultrasonography in the diagnosis of hydrocephalus keeping CT scan as a gold standard. Study design: Cross-sectional study Place and duration of study: Department of Pediatrics, Combined Military Hospital, Rawalpindi, from 01-01-2017 to 30-06-2017 Materials and Methods: A total of 121 children with a clinical diagnosis of hydrocephalus were selected and subjected to ultrasound of the head. Subsequently, a CT scan of the head was done and both modalities were compared. The diagnostic accuracy of the ultrasound was determined to keep CT findings as to the gold standard. Results: The mean age was 51.36 ± 34.01 days. The male gender was dominant as 81 (66.9%) patients were males. Ultrasonography of the head detected 93 (76.9%) patients with hydrocephalus while CT scan detected 90 (74.4%). Sensitivity, specificity, PPV, NPV and accuracy of USG to diagnosed hydrocephalus were 88.9%, 58.1%, 86.0%, 64.3% and 80.99% respectively Conclusion: Ultrasonography of head is a valuable screening tool for the diagnosis of hydrocephalus.